Aortic Isthmus Doppler Velocimetry in Fetuses with Intrauterine Growth Restriction: A Literature Review - Ferraz, Mariana Martins; Araújo, Flávia do Vale; Carvalho, Paulo Roberto Nassar de; Sá, Renato Augusto Moreira de (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Intrauterine growth restriction (IUGR) is associated with poor perinatal prognosis and a higher risk of stillbirth, neonatal death, and cerebral palsy. Its detection and the evaluation of its severity by new Doppler velocimetric parameters, such as aortic isthmus (AoI), are of great relevance for obstetrical practice. The AoI is a vascular segment that represents a point of communication between the right and left fetal circulations. It is considered to be a functional arterial shunt that reflects the relationship between the systemic and cerebral impedances, and has recently been proposed as a tool to detect the status of hemodynamic balance and prognosis of IUGR in fetuses. In the present review, we noticed that in healthy fetuses, the AoI net flow is always antegrade, but in fetuses with IUGR the deterioration of placental function leads to progressive reduction in its flow until it becomes mostly retrograde; this point is associated with a drastic reduction in oxygen delivery to the brain. The more impaired the AoI flow is, the greater is the risk of impairment in the Doppler velocimetry of other vessels; and the alterations of the AoI Doppler seem to precede other indicators of severe hypoxemia. Although there seems to be an association between the presence of retrograde flow in the AoI and the risk of long-term neurologic disability, its role in the prediction of perinatal morbi-mortality remains unclear. The AoI Doppler seems to be a promising tool in the management of fetuses with IUGR, but more studies are needed to investigate its employment in clinical practice.
Keywords: doppler velocimetry; doppler; aortic isthmus; intrauterine growth restriction; intrauterine growth retardation; placental insufficiency